PENDEKATAN PENDIDIKAN ISLAM DALAM MENGATASI KRISIS MORAL DAN ETIKA SISWA DI MDA NURUL HUDA CAMPAKA PANDEGLANG - Gopur, Abdul; Ilzamudin Ma’mur; Rifyal Ahmad Lugowi; Wasehudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The moral and ethical crisis among students is increasingly becoming a serious concern in the world of education today. Various problems such as bullying, dishonesty and misuse of technology reflect the lack of strong character formation in the younger generation. Islamic education, which is based on moral values ​​from the Koran and Hadith, offers a holistic approach in dealing with these problems. This article aims to examine the role of Islamic education in shaping the character of students through the application of Islamic moral and ethical teachings, which focus on noble character, consistency in worship, and the principles of justice. This approach not only focuses on intellectual aspects, but also strengthens students' positive character and behavior, which is expected to be a solution to the moral and ethical crisis that is occurring. It is hoped that this study can find effective methods in implementing Islamic education to form a young generation with integrity and responsibility.